Handbook of research on artificial immune systems and natural computing applying complex adaptive technologies - Mo, Hongwei, 1973- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
Today, nature is used as a source of inspiration for the development of new techniques for solving complex problems in various domains, from engineering to biology, with innovative adaptations under investigation. This work provides the latest empirical research findings, theoretical frameworks, and technologies of natural computing and artificial immune systems (AIS). A reference source for professionals, researchers, and academicians within the AIS and natural computing fields, this comprehensive collection written by leading international experts proposes new ideas, methods, and theories to solve problems of engineering and science.